Socio-economic status of mule producers and management practices of mule production in rural areas - PAL, YASH; LEGHA, R A (The Indian Journal of Animal Sciences, 2011)
The mules are widely used for carrying men and luggage in the hilly terrains and for pulling carts in the plains. Some people living on the banks of Yamuna and Ganga river rear mares for mule production. The study was planned to know socio-economic status of mule producers and managemental practices followed by theIn. The prin1ary data were collected from 50 mule producers belonging to Haryana, Uttar Pradesh and Uttarakhand states. The people engaged in mule production belong to mainly minority community. Majority of them were poor and illiterate. Mean family size was observed as 8.48Â±0.40. Mule producers sale mule foals in local animal fares and selling price varied from Rs 10000 to 40000. Contribution of women and children in mule production was significant. Non-availability of free grazing common land and loss of libido in donkey stallions were the major problems reported by the equine owners. They provided 3 to 4 kg concentrate per day to the donkey stallions during the winter. Most of the equine owners decanted the colostrums from the udder of the mare and did not allow the foals to suckle the colostrunl. Most of them were ignorant to diseases tetanus, glanders, rabies, influenza, herpes etc. and their prophylactic control. Problem of colic and worm infestations in their equines was very common. Equine owners showed keen interest in getting their mares artificially inseminated with the frozen semen of superior exotic donkeys for the production of superior n1ules because the equine owners were getting good prices from the sale of mule produced through AI.Â